From Prion Diseases to Prion-Like Propagation Mechanisms of Neurodegenerative Diseases - Isabelle Acquatella-Tran Van Ba; Thibaut Imberdis; Véronique Perrier (International Journal of Cell Biology)
Prion diseases are fatal neurodegenerative sporadic, inherited, or acquired disorders. In humans, Creutzfeldt-Jakob disease is the most studied prion disease. In animals, the most frequent prion diseases are scrapie in sheep and goat, bovine spongiform encephalopathy in cattle, and the emerging chronic wasting disease in wild and captive deer in North America. The hallmark of prion diseases is the deposition in the brain of PrPSc, an abnormal β-sheet-rich form of the cellular prion protein (PrPC) (Prusiner 1982). According to the prion hypothesis, PrPSc can trigger the autocatalytic conversion of PrPC into PrPSc, presumably in the presence of cofactors (lipids and small RNAs) that have been recently identified. In this review, we will come back to the original works that led to the discovery of prions and to the protein-only hypothesis proposed by Dr. Prusiner. We will then describe the recent reports on mammalian synthetic prions and recombinant prions that strongly support the protein-only hypothesis. The new concept of “deformed templating” regarding a new mechanism of PrPSc formation and replication will be exposed. The review will end with a chapter on the prion-like propagation of other neurodegenerative disorders, such as Alzheimer’s and Parkinson’s disease and tauopathies.